On subgroups of hyperbolic tetrahedral Coxeter groups - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2010)
In this work we address the problem on the determination of the subgroup structure of crystallographic groups in hyperbolic space by deriving the low index subgroups of hyperbolic tetrahedral Coxeter groups and tetrahedral Kleinian groups. This paper continues the work giv en in [5, 6] on the subgroups of triangle groups.